2023
DOI: 10.3390/pharmaceutics15041300
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Liver-on-a-Chip for Preclinical Drug Discovery

Abstract: Drug discovery is an expensive, long, and complex process, usually with a high degree of uncertainty. In order to improve the efficiency of drug development, effective methods are demanded to screen lead molecules and eliminate toxic compounds in the preclinical pipeline. Drug metabolism is crucial in determining the efficacy and potential side effects, mainly in the liver. Recently, the liver-on-a-chip (LoC) platform based on microfluidic technology has attracted widespread attention. LoC systems can be appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…These devices provide a more representative physiological environment compared to 2D assays, enabling us to study a particular phenomenon in models that closely resemble those found in living organisms. Indeed, they offer a valuable alternative for studying, e.g., cellular behavior, drug responses in disease models, providing meaningful insights, and generate more straightforward and conclusive human-related data that contribute to reducing the number of animals used in research. Microfluidic-based cell cultures present numerous advantages, such as allowing a dynamic and controlled environment (e.g., chemical gradients, flow rate, shear stress, pH, CO 2 , O 2 , or temperature), the continuous inflow of nutrients by perfusion, regular waste removal, less consumption of fluids, automated liquid handling systems (e.g., pumps), and the possibility of integration with biosensors . Therefore, microfluidic systems are increasingly being used as resourceful tools and valuable alternatives to traditional approaches.…”
Section: Microfluidic Devicesmentioning
confidence: 99%
“…These devices provide a more representative physiological environment compared to 2D assays, enabling us to study a particular phenomenon in models that closely resemble those found in living organisms. Indeed, they offer a valuable alternative for studying, e.g., cellular behavior, drug responses in disease models, providing meaningful insights, and generate more straightforward and conclusive human-related data that contribute to reducing the number of animals used in research. Microfluidic-based cell cultures present numerous advantages, such as allowing a dynamic and controlled environment (e.g., chemical gradients, flow rate, shear stress, pH, CO 2 , O 2 , or temperature), the continuous inflow of nutrients by perfusion, regular waste removal, less consumption of fluids, automated liquid handling systems (e.g., pumps), and the possibility of integration with biosensors . Therefore, microfluidic systems are increasingly being used as resourceful tools and valuable alternatives to traditional approaches.…”
Section: Microfluidic Devicesmentioning
confidence: 99%
“…They can demonstrate the effects of different substances, drugs, and mechanisms 20 . These simulated platforms, by better simulating physiological conditions and better drug efficiency prediction using sophisticated in vitro models, have bridged the gap between data from animal and human studies 21 – 23 . MFC devices provide distinct advantages over conventional in vitro cell culture methods, by better regulating the micro environmental factors, such as fluid flow, shear stress, and gradients of nutrients and oxygen, that significantly impact the cellular behavior and the results of drug screening experiments 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%